Exploring various metal-ligand coordination bond formation in elastomers: Mechanical performance and self-healing behavior - M. Das; S. Pal; K. Naskar (eXPRESS Polymer Letters, 2020)
Dynamic covalent crosslinking such as disulfide bonds, Diels-Alder (DA) reactions are widely used for healing applications. Herein, we report a simple approach involving the metal-ligand reversible interactions in diverse nature, which helps in developing a robust and self-healable carboxylated nitrile (XNBR) rubber by employing low cost and the commercially obtainable materials. Self-healing performance and mechanical properties were organized by introducing the various metal-ligand domains into the XNBR rubber. The network of XNBR, in-situ cross-linked via metal-ligand complexes, consists of strong and weak coordination bonds. The strength of various metal-ligand modified coordination bonds, healing performance, and mechanical properties primarily depend on the type of metal ions. The Fourier transform infrared spectroscopy (FTIR) makes the various metal-ligand coordination bond formation into the XNBR rubber visible. The coordination crosslinked XNBR rubber with 4 phr of Zn and Co metal ion exhibits high tensile strength (4.3±0.6 and 10.3±1.1 MPa) with excellent healing efficiency (100 and 88%), which is far higher than the most reported non-covalent supramolecular modified elastomers. The various metal-ligand coordination bonds are fully reconstructed during the rebuilding process and exhibiting excellent self-healing property.